The Impact of the MBG (Free Nutritious Meal) Program in Palembang City: Dampak Program MBG (Makan Bergizi Gratis) di Kota Palembang - Sari Riski Novianti; Amaliatulwalidain (Universitas Indo Global Mandiri, 2026)
Purpose: This study aims to analyze the impact of implementing the Free Nutritious Meal (MBG) Program in Palembang City on students' nutritional fulfillment and its implications for learning concentration. Methodology: Employing a qualitative approach with a descriptive method, data were gathered through interviews, observations, and documentation, followed by systematic analysis involving data reduction and presentation. Findings: The findings reveal that the MBG Program contributes positively to daily nutritional adequacy and student focus. Nevertheless, operational challenges persist, including limited menu variety, uneven distribution, and the necessity for enhanced cross-sectoral coordination. Practical Implications: Practically, this study offers strategic recommendations for local governments to evaluate distribution governance and nutritional standardization to ensure policy sustainability. Originality/Value: The originality of this research lies in its empirical analysis of local implementation of national education policies. As a research paper, this study underscores the urgency of nutritional interventions in holistically improving human resource quality. Paper type: Research Paper